Bibliometric Analysis of Design Thinking in Engineering Education: Trends and Scientific Evolution (2014-2024) - León Espinoza, Ivonne Priscilla; Solórzano Vargas, Christian Fidel; Molina Barzola, Mónica (LACCEI, 2025)
Design Thinking has emerged as a key methodology in engineering education, fostering creativity, problem-solving, and learning through experimentation. This study presents a bibliometric analysis of the scientific production on Design Thinking in the context of engineering education over the past decade (2014–2024), using data extracted from the SCOPUS database.Bibliometrix in R was employed to analyze key indicators, including the evolution of the number of publications, the most influential authors, and keyword co-occurrence. The results indicate a significant increase in scientific production, with a notable rise in recent publications, highlighting the contributions of leading authors and universities in the field. Additionally, emerging trends were identified in the application of Design Thinking in innovative teaching strategies, such as project-based learning and competency-based approaches.This study provides a quantitative perspective on the development of research in this area, emphasizing opportunities for future studies and applications in engineering education.